2002
DOI: 10.1128/jvi.76.4.1649-1662.2002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Design Architecture for Genetic Stability of Recombinant Poliovirus: the Manipulation of G/C Contents and Their Distribution Patterns Increases the Genetic Stability of Inserts in a Poliovirus-Based RPS-Vax Vector System

Abstract: Poliovirus has been studied as a live recombinant vaccine vector because of its attractive characteristics. The genetic instability, however, has hampered recombinant polioviruses (PVs) from being developed as an appropriate vaccine. A variety of different foreign inserts were cloned directly into our poliovirus Sabin 1-based RPS-Vax vector system, resulting in the production of recombinant PVs. The genetic stability of each recombinant PV was examined during 12 rounds of consecutive passage. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 46 publications
2
25
1
Order By: Relevance
“…2B), and sequencing of 15 individual clones showed that the epitopes were intact. The reason for the unusual stability of this sequence is not clear; others have proposed that a high G/C content confers stability on poliovirus inserts (29), but our data do not allow us to draw conclusions regarding the insert in rCVB3.6. However, we can conclude that the low immunogenicity of rCVB3.6 is unlikely to be caused by the rapid loss of epitope sequence.…”
Section: Discussioncontrasting
confidence: 46%
“…2B), and sequencing of 15 individual clones showed that the epitopes were intact. The reason for the unusual stability of this sequence is not clear; others have proposed that a high G/C content confers stability on poliovirus inserts (29), but our data do not allow us to draw conclusions regarding the insert in rCVB3.6. However, we can conclude that the low immunogenicity of rCVB3.6 is unlikely to be caused by the rapid loss of epitope sequence.…”
Section: Discussioncontrasting
confidence: 46%
“…Rapid recombination also appears to be an underlying cause of the instability and deletion of foreign, nonviral sequences from recombinant viral RNA vectors (6; reviewed in 7). Genome instability presents one of the most important obstacles to the use of recombinant RNA viruses as gene expression vectors for various practical applications, including gene therapy (8)(9)(10).…”
mentioning
confidence: 99%
“…Linearized plasmid DNA was transcribed in vitro with T7 RNA polymerase (NEB) for 1 h at 37 • C. Template DNA was eliminated after transcription with RNase-free DNase I (NEB) for 30 min at 37 • C. Transcripts were transfected into HeLa cells with DEAE-dextran process as described previously [22]. When cytopathic effects (CPEs) were observed, supernatants were transferred into fresh HeLa cell cultures to amplify progeny viruses.…”
Section: Production Of Rec-pvsmentioning
confidence: 99%
“…Foreign inserts have been integrated and expressed from the poliovirus Mahoney-originated vector [19,21], or poliovirus Sabin 3-based vector [20]. We have constructed and reported a recombinant poliovirus Sabin 1-based vaccine vector named RPS-Vax system [22]. This vector has multiple cloning sites and an artificial 3C protease-recognition site at the N-terminal end of the Sabin 1 polyprotein.…”
Section: Introductionmentioning
confidence: 99%